ECOLOGICAL AND REPRODUCTIVE ASPECTS OF THE EXOTIC PLECO HYPOSTOMUS CF. NICEFOROI (SILURIFORMES: LORICARIIDAE), NORTHERN ATLANTIC SLOPE OF COSTA RICA - Castillo-Pérez, Damian (2026)
The aim of this study was to know the invasion stage of the suckermouth armored catfish Hypostomus cf. niceforoi, in the Sabogal River, located northern Atlantic slope of Costa Rica. Between October 2017 and May 2018, the fishes were caught monthly with a cast nest. In total, 663 fishes belonging to 21 species and ten families were identified, which weighed 74 541 g. Each individual H. cf. niceforoi was collected and incised ventrally to determine its sex, gonadal maturity stage and total number of mature oocytes. The species that recorded the highest abundance and total biomass was H. cf. niceforoi (n = 152 individuals, and 27 666 g, respectively). It was reproductively active during the entire study period (total fecundity varied from 318 to 748 mature oocytes per female), including rainy and dry season. The males were larger than the females. This fish has reached stage V of invasion (widespread and dominant). The conservation effort in the Sabogal River should implement the local management of H. cf. niceforoi and periodically assess its population.